A língua inglesa no ensino secundário brasileiro: 1838-1930 - Jucá , Ricardo Westphalen de Queiroz (2010)
This study examined the trajectory of the English language as a school discipline in Brazilian secondary education in 1838 to 1930. Given the impossibility of studying this trajectory in Brazilian secondary education as a whole, the analysis focused on teaching in Collegio of Pedro II, as the default for the institution counterparts. Therefore, initially sought to characterize the sociopolitical environment and educational which enabled its institutionalization as school discipline, as well as their integration into curriculum of the Imperial Collegio of Pedro II. Then we tried to explain how the discipline was in terms of content and methodology in the different study plans adopted in the period in question in the theoretical aspect-methodological sedans study in the History of School Culture, the History of School Subjects. The main sources used were Curricula, Educational Programmes, the class hours, the textbooks adopted as a result of each educational reform implemented in that period College.The study has showed that the English language was into the study plans of Collegio of Pedro II since their inclusion in 1838 until 1930, and the importance attributed to it, under the study plans changed little over the studied period. However, in the course of this period there were observed significant changes in the purpose of its education and consequently in the content of the textbooks, as well as in the adopted methodology. If initially the ' grammar translation was adopted, considered the first methodology applied to language teaching, gradually the adoption of methodological innovations by introducing techniques as oral practice, a guidance to the teacher who should use only English language in the classroom, greater emphasis on dramatic reading and pronunciation exercises, which announced a new vision of education by calling its method the “direct method”.